Memetized Learning: How Humor-Infused Stories Can Engage Geography Students in the Digital Age - Kudzayi Savious Tarisayi (Universitas Pendidikan Indonesia (UPI), 2024)
Scholars have long recognized the power of traditional storytelling for engaging students and enhancing the learning experience. This study explores how integrating memes into storytelling, creating